Experimental Validation of the Innovative Thermal Energy Storage Based on an Integrated System "Storage Tank/Steam Generator". (May 2015) - Gaggioli, W.; Fabrizi, F.; Tarquini, P.; Rinaldi, L.
Abstract: In the past years, an innovative thermal energy storage system at high temperature (up to 550̊C) for CSP plants was proposed by ENEA and Ansaldo Nucleare: a single storage tank integrated with a steam generator immersed in the heat storage medium. The idea is based on the exploitation of the thermophysical characteristics of the heat storage medium (a binary mixture of salts of NaNO3 at 60% and KNO3 at 40%) in order to maintain over time, in the single tank, a thermal stratification of the fluid. The thermal stratification is able to trigger, in the immersed steam generator, the natural circulation, shell side and downwards, of the hot molten salt cooled down by the water that flows upwards tube side, thus heating up and producing superheated steam. The advantages of such a system are: - efficient performances; - simple implementation; - compactness: - modularity; - and, overall, contained costs: only one storage tank instead of the two tanks and only one heat exchanger instead of the three exchangers of the classic configuration; reduced quantity of salt; minimization of piping, valves and other components. The technical feasibility of the proposed system, together with the stability over time of the stratification in temperature of the storage medium, have been already verified and assessed. This report has the aim of presenting the experimental results obtained by ENEA in the Casaccia Research Centre (Rome, Italy), with a small scale test section consisting of a 300 kWth steam generator inserted in a 8 m 3 storage tank with molten salt at high temperature. The reported results relate to the behaviour of the system in steady state conditions, and show its promising performances.